RESSIGNIFICANDO TRAJETÓRIAS: a Justiça Restaurativa como prática no âmbito do ato infracional pelo Ministério Público no Maranhão - PINTO, Carla Costa (2016)
This work has as main objective to analyze the relevance of the application of restorative practices within the offense, from the work of the Prosecutor’s Office of the State of Maranhao, based on the analysis of the current context of the Rights of Children and Adolescents, the handles teen author of an offense, the role of specialized justice prosecutor in childhood and youth and observation brazilian experiences that have already developed work in the field of restorative justice as a way to draw a possibility of developing a model in São Luis, specifically considering the Integrated Center for Juvenile Justice. Counting, therefore, to conduct field research conducted in Maranhao, Para, Sao Paulo and Rio Grande do Sul.